ANIMASI PADA RELIEF RAMAYANA CANDI SIWA - Setyawan, Alfan (Seni Media Rekam ISI Surakarta, 2017)
Shiwa Temple is one of the temples located in the Prambanan temple complex, where Prambanan temple is one of the world cultural heritage located in Indonesia. On the Shiva temple there is a relief that tells epos about Ramayana.In that time,the relief become one of the efective visual media to tell stories such as the media animation in the present.Seeing from thevisualization apparently,the relief of Shiva temple has its own uniqueness and indicated to have the concept of modern animation form.This research has a purpose to know relief form and concept of animation on relief of Shiva temple.The sample of this research is taken from a Ramayana relief panel located in Shiva temple, where according to the writer, that panel hasenough visual characteristic to explain the concept of animation.The results of this study reveal the elements of the shape of the relief Ramayana on Shiva temple and the form of animated concepts applied to the relief of Shiva temple.Keywords: Relief,Ramayana,animation,and Shiva temple